Determination and Optimization of Vitamin B Complex (B1, B2, B3 and B6) in Cellulase Treated Polished Rice by HPLC with UV Detector - Kothakota, Anjineyulu; Pandiselvam, Ravi; Rajesh, G.K.; Gowthami, K. (Asian Journal of Chemistry, 2016)
A novel processing technology is developed to polish rice in a more selective way with the help of cellulase enzyme of microbial sources. The enzyme were produced from Trichoderma reese, MTCC164. Brown rice was treated with enzyme concentration of 60-100 % (40 mL of buffer-undiluted) for 30 to 150 min (with variation of 30 min) at 30 to 50 °C (with variation of 5 °C) to attain a saturated moisture level. Selective degradation of bran layers in enzymatic polished rice (polishing time 20-100 s with variation of 20 s) has facilitated the retention of more thiamine, riboflavin, pyridoxine and niacin nutrients compared to normal milled rice. The retention of vitamin B complex nutrients detected through HPLC with UV detector and optimized by response surface methodology (RSM) with central composite design. The optimized enzyme treated bio-polished rice better sources of thiamine (51 %), riboflavin (48 %), pyridoxine (90 %) and niacin (54 %) concentration over mechanically milled rice.